Expansion of Religious Pluralism in Korean Civil Society: A Case Study of Conscientious Objection in South Korea - Yoo, Kwang Suk (Religions, 2018)
This paper analyzes a socio-cultural adaptation of the concept of religious pluralism, focusing on the matter of conscientious objection in Korean pluralistic situation. The issue of conscientious objection in Korea has extended from a religious and philosophical field to a political, diplomatic, and international problem, being influenced heavily by IRFR and UNHRC. Regardless of their numerical marginality, its social implication is revealed more clearly in recent decisions of local or higher courts and triggers another significant public discourse on how Korean civil society should expand a concept of pluralism to integrate them. The paper concludes that the concept of pluralism advances into an operational principle to prop up the civil society of Korea beyond the narrow concept of religious pluralism.